Kuuvan̳miut subsistence : traditional Eskimo life in the latter twentieth century - Anderson, Douglas D.; United States. National Park Service. ([Washington, D.C.?] : National Park Service, Dept. of the Interior, 1998)
Mode of access: Internet.